2023
DOI: 10.1002/anie.202309043
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Cancer Resistance to Platinum Drugs by Inhibiting Cholesterol Metabolism

Ying Wang,
Linxiang Cai,
Hui Li
et al.

Abstract: Drug resistance is a serious challenge for platinum anticancer drugs. Platinum complexes may get over the drug resistance via a distinct mechanism of action. Cholesterol is a key factor contributing to the drug resistance. Inhibiting cellular cholesterol synthesis and uptake provides an alternative strategy for cancer treatment. Platinum(IV) complexes FP and DFP with fenofibric acid as axial ligand(s) were designed to combat the drug resistance through regulating cholesterol metabolism besides damaging DNA. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…26 A recent study by another group also reported two Pt( iv ) compounds, FP and DFP, utilizing fenofibric acid as an axial ligand to regulate cholesterol metabolism and damage DNA, thereby addressing drug resistance. 72 These two complexes generate reactive oxygen species, induce DNA damage, inhibit cholesterol accumulation, and promote cholesterol efflux. 72 Additionally, they upregulate PPARα and activate gasdermin D (GSDMD) and caspase-1, thereby stimulating apoptosis and pyroptosis in cancer cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…26 A recent study by another group also reported two Pt( iv ) compounds, FP and DFP, utilizing fenofibric acid as an axial ligand to regulate cholesterol metabolism and damage DNA, thereby addressing drug resistance. 72 These two complexes generate reactive oxygen species, induce DNA damage, inhibit cholesterol accumulation, and promote cholesterol efflux. 72 Additionally, they upregulate PPARα and activate gasdermin D (GSDMD) and caspase-1, thereby stimulating apoptosis and pyroptosis in cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…72 These two complexes generate reactive oxygen species, induce DNA damage, inhibit cholesterol accumulation, and promote cholesterol efflux. 72 Additionally, they upregulate PPARα and activate gasdermin D (GSDMD) and caspase-1, thereby stimulating apoptosis and pyroptosis in cancer cells. By reducing cholesterol levels in cancer cells, these complexes significantly alleviate drug resistance and exhibit remarkable in vitro and in vivo anticancer effects, especially in cisplatin-resistant cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, the two axial ligands introduced in platinum(IV) complexes could be used to promote tumor-targeting ability or bioavailability and enhance cellular uptake, respectively. , Therefore, multifunctional platinum(IV) complexes are an effective strategy to enhance antitumor efficacy, overcome the drug resistance, and reduce the side effects of the conventional platinum(II)-based drugs because of the different mechanism of antitumor action. For example, multifunctional platinum(IV) complexes (Figure ), such as CX-4945-platinum(IV), chalcone-platinum(IV), , chlorambucil-platinum(IV), BBI-608-platinum(IV), pterostilbene-platinum(IV), evodiamine-platinum(IV), fenofibric acid-platinum(IV), ketoprofen-platinum(IV), PARPis-platinum(IV), and so on, not only displayed stronger antitumor activity than that of cisplatin both in vitro and in vivo but also exhibited low toxicity toward normal tissue in cisplatin-sensitive or -resistant tumor xenograft models. Therefore, exploring a multifunctional platinum(IV) prodrug with liver-targeting ability is an ideal strategy for the development of potential anti-HCC drugs.…”
Section: Introductionmentioning
confidence: 99%
“…The regulation of cholesterol by activating peroxisome proliferator activating receptors (PPARs) has received extensive attention . Gemfibrozil (GFB) is a prototype activator of PPARα (an isotype of PPARs) and approved by the FDA for clinical use to lower blood lipids .…”
Section: Introductionmentioning
confidence: 99%